3. Penyediaan Jasa Keuangan Mikro Secara Berkelanjutan di Indonesia: Tinjauan Teoritis dan Empiris - Ketut Budastra (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2007)
Abstract Microfinance development has become a fundamental element of policies addressing poverty alleviation and income distribution issues in Indonesia. However, how to develop the microfinance sector remains a controversial issue in both theory and practice. In this regard, this article attempts to draw some lessons (from the controversy) useful for microfinance development in Indonesia. Theoretical perspectives indicate that the level of microfinance development is determined by a number of factors, including: the characteristics of the microfinance institutions, microfinance policies, and demographic-economic-socio-cultural and infrastructure environments. Practical perspectives suggest that developing the service outreach and service efficiency of existing microfinance institutions is a wiser strategy than developing new ones, particularly, in dense areas such as Java, Bali and Lombok. Elimination of distorting factors gives the opportunities for developing a sustainable and wide service outreach micro-credit system in Indonesia. A closer look to development of major microfinance institutions in Nusa Tenggara Barat Province suggests as follows. BRI Unit need to develop new services to deepen its service outreach, reaching lower class of population in the income distribution ladder. Bank Perkreditan Rakyat need to improve their operational scale, management, service methodology and competitive standing in the market. Efforts to further develop LKP need to focus on the less performing ones Abstrak Pembangunan kredit mikro telah menjadi komponen mendasar dalam kebijakan pembangunan ekonomi yang beradilan sosial dan pengentasan kemiskinan di Indonesia. Namun bagaimana membangun LKM masih merupakan isu kontroversial dalam teori maupun praktis. Paper ini berupaya untu menjawab pertanyaan penting tersebut dengan menarik pemebelajaran dari teori and pengalaman pratis. Perspektip teoritis terkini menyarankan bahwa tingkat perkembangan LKM dipengaruhi oleh banyak faktor, baik faktor internal maupun eksternal. Pengalaman praktis Indonesia menunjukan bahwa pemberlakuan tingkat bunga pasar dan penyederhanaan persyaratan dan prosedur pembukaan LKM baru telah menghasilkan jumlah LKM yang relatip banyak. Keadaan ini menyarankan bahwa mengembangkan luas cakupan pelayanan dan effisiensi ribuan LKM yang telah ada—dengan menghilangkan rintangan-rintangan yang ada– adalah pilihan strategi yang lebih bijaksana daripada mencoba atau membangun lembaga baru di daerah-daerah dengan kepadatan LKM tinggi. Tinjuan lebih dekat terhadap tiga jenis LKM utama yang beroperasi di NTB (BRI unit, BPR swasta dan LKP) menyarankan sebagai berikut. Upaya pengembangan BRI unit hendaknya diarahkan pada pengembangkan luas cakupan pelayannya, khususnya melalui pengembangan produk pelayanan untuk kelompok rakyat kecil. Pengembangan BPR hendaknya diupayakan dan diarahkan pada peningkatan skala usahanya, management, teknologi pelayanan, dan daya saing, diantaranya melalui merger BPR kecil, memaksimasi peranan organisasi pendukung, dan perbaikan supervisi. Pengembangan LKP hendaknya diarahkan pada LKP berpenampilan buruk, disamping maksimasi luas cakupan pelayanan LKP berpenampilan baik.